Comunicação para alteridade: a propaganda social em rede como responsividade à figura do Outro - Janjacomo, Caroline (Universidade Federal de São Carlos, 2019)
This work aims to understand the potential of alterity in the discourses of social propagandadisseminated in a network. For this, we seek to highlight social propaganda as a specific discursive genre - which takes care of propagating socially relevant content - and to reflect about the use of digital media in this type of propaganda campaign. In this way, we rely essentially on Mikhail Bakhtin's studies philosophy of language, interweaving their conceptsto authors who, together with the latter, problematize the figure of the Other in the relations held in the context of cyberspace. Subsequently, we apply the reflections to studies about social propaganda, differentiating this from other parallel communicationals genres. Through these theoretical structures, we deepened the discussion of this genre through the campaign "Ice Bucket Challenge", which, disseminated in the networks of cyberspace, aimed to awaken senses of alterity in contemporary society and developed itself as a response to the relationship between the Self and the Other carried out in this environment.
Communication to otherness: the social propaganda in network as responsiveness to the figure of the Other
Keywords: Propaganda social; Alteridade; Ciberespaço; Responsividade; Social propaganda; Alterity; Cyberspace; Responsiveness; Bakhtin, M. M. (Mikhail Mikhailovitch), 1895-1975; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO; LINGUISTICA, LETRAS E ARTES